Preparation of Nano-Antigen for Brucella Abortus by Ultrasound Technique and Evaluate their Sensitivity by ELISA Technique (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The nanoparticle technology, or nanotechnology is the science that studies the treatment ofmatter on the atomic and molecular scale. Nanotechnology deals with measurements between 1 to 100nanometers, i.e. deals with atomic clusters ranging from five atoms to a thousand atoms. They are muchsmaller than bacteria and a living cell palsy.Method: In this study, it involved the production of a new technique for diagnosing infection with Brucellabacteria. This study included 45 samples of patients suffering from brucellosis (women and men), in additionto 36 samples from other Brucella. All were diagnosed Injuries by hospital medical advisory staff usingvarious tests vitek, ELISA, API20C, Morphology, Brucella media test. The samples were examined usingthe new technique compared to the routine method of diagnosis. We found that the new technique gave apositive result to the samples infected with Brucella bacteria, while the rest of the samples without infectionwith Brucella bacteria gave a negative result.Results: It was found that the tests of Elisa and API20C, Vitek were more sensitive 100% and specialized100% for the diagnosis of Brucella bacteria than other method morpholgy with allergic 44%and specialized86%, Brucella mediaTest, with allergy 88 % And specialty 86%. The results of the ELISA kit test were thenano-labs (the new technique) in this study to diagnose more successful bacteria compared to normal systemand more allergic and specialized because of the antigen-containing.Conclusion: The new kit use in nanotechnology is more Sensitivity and Specificity for diagnosis to thebrucella, Roads routine to diagnose brucella is not effective compared with API, Vitek and ELISA .